Is participation in after-school physical activity associated with increased total physical activity? A study of high school pupils in the Czech Republic - Pelclová, Jana; El Ansari, Walid; Vasícková, Jana (International journal of environmental research and public health, 2010)
This study assessed the physical activity (PA) levels and its variability across days, months and seasons of two groups of high school pupils: those who did and those who did not participate in regular organized after-school physical activity (ASPA). Thirteen pupils wore pedometers continuously for one school-year, logged their step counts into record sheets and were then interviewed for information as regards their participation in any ASPA. Repeated measures analysis of variance showed that regardless of the day, month and season, ASPA pupils achieved significantly more mean step counts/day than the non-ASPA pupils. There were no significant fluctuations across months and seasons in PA levels of ASPA pupils when compared to non-ASPA pupils. We conclude that regular organised ASPA might increase the pupils' total PA levels; and could help to maintain a relatively constant PA level for adolescents across the whole school-year regardless of the influences of a range of weather and meteorological indicators that are related to months/seasons.
Keywords: Circadian Rhythm; Seasons; day, month and season variability; longitudinální studie; adolescents; physical education; cvičení; mladiství; cirkadiánní rytmus; Česká republika; školy; mužské pohlaví; studenti; Czech Republic; Schools; ženské pohlaví; Humans; Students; self-determined physical activity; pedometer; Exercise; Longitudinal Studies; Female; roční období; Adolescent; lidé; Male